2008
DOI: 10.1002/aoc.1374
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dimethyltin(IV) dichloride with 5′‐IMP and 5′‐UMP

Abstract: The formation constants of the species formed in the systems H + + dimethyltin(IV) + 5 -IMP and 5 -UMP, H + + 5 -IMP and H + + 5 -UMP have been determined in aqueous solution in the pH range 1.5-9.5 at constant temperature (25• C) and constant ionic strength (0.1 mol dm −3 NaClO 4 ), using spectrophotometric and potentiometric techniques. 1 H and 31 P NMR investigations in aqueous solution confirmed the species formation. The precipitated complexes of IMP and UMP by Me 2 Sn(IV) 2+ at low pH values were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Other studies pointed to the direct interaction of diorganotins with the phosphate backbone of DNA leading to DNA damage through a change of conformation . Given the different possible mechanisms of actions, the interactions of the organotin compounds with several biologically relevant species such as amino acid or nucleic acid building blocks have been performed. More particularly, NMR studies of aqueous solutions of diethyltin­(IV) dichloride with 5′-CMP, 5′-dCMP, 5′-UMP, 5′-IMP, and 5′-GMP indicated that, below pH 4, the diethyltin­(IV) moiety is involved in bonding with the phosphate group of the nucleotides. At pH > 9.5, the Et 2 Sn­(IV) moiety was found to react with the O(2′) and O(3′) oxygen atoms of the sugar unit of the nucleotide, whereas at intermediate pH values (4.0–9.5), there was no evidence for interaction with the nucleotide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies pointed to the direct interaction of diorganotins with the phosphate backbone of DNA leading to DNA damage through a change of conformation . Given the different possible mechanisms of actions, the interactions of the organotin compounds with several biologically relevant species such as amino acid or nucleic acid building blocks have been performed. More particularly, NMR studies of aqueous solutions of diethyltin­(IV) dichloride with 5′-CMP, 5′-dCMP, 5′-UMP, 5′-IMP, and 5′-GMP indicated that, below pH 4, the diethyltin­(IV) moiety is involved in bonding with the phosphate group of the nucleotides. At pH > 9.5, the Et 2 Sn­(IV) moiety was found to react with the O(2′) and O(3′) oxygen atoms of the sugar unit of the nucleotide, whereas at intermediate pH values (4.0–9.5), there was no evidence for interaction with the nucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, on one hand, an experimental study about the interaction of dimethyltin(IV) with 5′-UMP indicated that the dimethyl tin moiety would not interact with the N3 atom of the uracil nucleobase but instead would be involved in a bidentate interaction with the phosphate group. 16 On the other hand, the formation of 1:1 complexes between dipropyltin(IV) and nucleobases through release of a hydrogen atom has been reported, including for uracil (deprotonated at the N3 position, Scheme 1). 18 In this context, a better understanding at the molecular level of the interactions between OTCs and DNA building blocks is thought to be helpful.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as for many drugs used in chemotherapy, they may have undesirable side effects. Therefore, understanding the interaction of OTC with possible biological targets is highly desirable, and this has led to a growing interest in the studies dealing with their interactions with different naturally occurring ligands, such as carbohydrates, nucleic acid derivatives, amino acids and peptides …”
Section: Introductionmentioning
confidence: 99%
“…Organotin compounds have been shown to have high antitumor activity in vitro in a wide variety of human tumors. The increasing interest in the chemistry and biochemistry of organotin complexes has led to extend studies on their interactions with different naturally occurring ligands, for example, carbohydrates, nucleic acid derivatives, amino acids, and peptides. ,, Several papers have revealed the coordination behavior of organotin cations toward biomolecules containing different types of donor atoms including both solid state and solution studies. …”
Section: Introductionmentioning
confidence: 99%